Dynamic Equilibrium Masyarakat Lintas Agama di Jawa dan Bali - Hanur, Binti Su’aidah; Lestari, Ike Rahayu Margi; Supriati, Binti (Proceedings of Annual Conference for Muslim Scholars, 2023)
Ethnic groups, languages, religions and beliefs are something risky to discuss since a long time of periods. The plurality and tolerance also shows difference level among countries. Religious moderation as a legal model of social integration in Indonesia has been published since 2019. this study aims to deeply reveal the best practices of dynamics social integration that occured in Indonesia especially in Kediri and Bali. This research was conducted using a qualitative method, using a multisite study approach. Data was collected by using observation and interview methods and using relevant documents sources. The result of this study shows that when the local government does not interfere towards their social life so much, the interfaith relations has positive reversible at equal rate. The result also shows that the community itself is able to unite and build social harmony as well as when it was bridged by the local government as in other cities.